2014
DOI: 10.4184/asj.2014.8.6.735
|View full text |Cite
|
Sign up to set email alerts
|

C1-C3 Lateral Mass Screw-Rod Fixation and Fusion for C2 Pathologies and Hangman's Fractures

Abstract: Study DesignRetrospective clinical study.PurposeWe report our experience of eight patients treated with C1-C3 lateral mass rod-screw stabilization and fusion in the treatment of Hangman's fracture and other axis pathologies.Overview of LiteratureDifferent surgical approaches, both anterior and posterior, have been described for treating Hangman's fracture and other pathologies where surgery is indicated.MethodsAll patients who underwent surgical treatment for Hangman's fracture and axial pathology where C1-C3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“… 32 In an exciting series, Chowdhury et al treated eight patients with Hangman's fractures using C1–C3 lateral mass screws while skipping C2 instrumentation, and their results were promising. 33 This technique becomes much more popular if the anatomical properties of C2 are unfit for instrumentation or the surgeon is not experienced in direct C2 instrumented fixation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 32 In an exciting series, Chowdhury et al treated eight patients with Hangman's fractures using C1–C3 lateral mass screws while skipping C2 instrumentation, and their results were promising. 33 This technique becomes much more popular if the anatomical properties of C2 are unfit for instrumentation or the surgeon is not experienced in direct C2 instrumented fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Elliott et al reviewed transarticular screws (TASs) and different screw‐rod constructs (SRCs) for posterior C1‐C2 fixation and found almost equal efficacy and safety of both techniques 32 . In an exciting series, Chowdhury et al treated eight patients with Hangman's fractures using C1–C3 lateral mass screws while skipping C2 instrumentation, and their results were promising 33 . This technique becomes much more popular if the anatomical properties of C2 are unfit for instrumentation or the surgeon is not experienced in direct C2 instrumented fixation.…”
Section: Discussionmentioning
confidence: 99%
“…None of the patients deteriorated after surgical intervention. Other studies, 19 have shown that lateral mass screw-rod fixation followed by fusion shows promise as an effective and biomechanically sound way of treatment in properly selected cervical injury cases.…”
Section: Discussionmentioning
confidence: 99%
“…Posterior C1-C3 screw fixation has been reported, and this technique can provide firm stabilization of the cervical spine. However, it is not considered desirable since resulting in a significant loss of intact C1-C2 activity [7]. By contrast, the combined of C2 pedicle (pars) screw and C3 lateral mass screw or C2-C3 pedicle screw fixation is a more effective fixation technique.…”
Section: Introductionmentioning
confidence: 97%